Análisis de Eficiencia de Sector Inmobiliario (2020)
This research an analysis of the efficiency of the real estate sector of the city of Cartagena - Colombia is developed. For the 46 companies registered as real estate agencies in the city, the techniques of principal components, data envelopment analysis and logistic regression were articulated. The results show an average efficiency of the sector of 42.33%, considering 8 companies as efficient. Five hypotheses were raised about the incidence of each financial item in the efficiency result, evidenced through the logistic regression model how the variable Operational Income is the only significant one (Value-p = 0.028). It was evidenced as an efficient real estate company should not have high values in the items of heritage and plants, property and equipment.